2018
DOI: 10.1159/000447223
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding the Obturator Jerk during TURBT

Abstract: Introduction: Bladder cancer is the seventh most common cancer in the UK. Transurethral resection of bladder tumor (TURBT) is a relatively common procedure used to treat cancer of the bladder. A serious complication of TURBT is bladder perforation, the risk of which is greatly increased in the presence of an “obturator jerk”. Methods: A literature search was performed on PubMed using the following search criteria “obturator nerve block”, “obturator nerve block in transurethral resection of bladder tumor”, “add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
(18 reference statements)
0
19
0
1
Order By: Relevance
“…When the electric current transmitted by the resectoscope directly stimulates the obturator nerve, an obturator reflex may occur [9]. The result of this reflex is adductor muscle contraction which may lead to bladder perforation [10]. The most notable finding in our study is that the incidence of bladder perforation observed in the PK group was about half that in the TURis group.…”
Section: Discussionmentioning
confidence: 64%
“…When the electric current transmitted by the resectoscope directly stimulates the obturator nerve, an obturator reflex may occur [9]. The result of this reflex is adductor muscle contraction which may lead to bladder perforation [10]. The most notable finding in our study is that the incidence of bladder perforation observed in the PK group was about half that in the TURis group.…”
Section: Discussionmentioning
confidence: 64%
“…During the resection of the bladder tumors, it is common to see the occurrence of obturator reflex. Obturator jerk increases the risk of some complications, such as incomplete resection, bladder perforation, the inability to give intravesical chemotherapeutic agents, extravesical dissemination of the tumor, and vascular injuries (12). Most urologists are concerned about some possible complications that may occur during resection of lateral wall-located bladder tumors when obturator nerve is close to lateral wall in its intrapelvic course (19).…”
Section: Discussionmentioning
confidence: 99%
“…Obturator nerve originates from the lumbar plexus of L2 to L4 and both motor and sensory nerve fibers passes through the obturator foramen of the pubis to innervate the adductor muscles of the thigh. It comes to close proximity to the prostatic urethra, bladder neck, and inferolateral bladder wall (12). Garcia Rodriguez et al reported that 46.8% of all bladder tumors are located at the lateral wall of the bladder (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 23 ] Although most urologists prefer GA for endoscopic renal surgery, RA has equivalent efficacy and safety outcomes with possibly reduced operative time, hospitalization stay, blood transfusion rates, and postoperative pain without compromising stone clearance rates. [ 24 25 26 27 ]…”
Section: Anesthesia Considerationsmentioning
confidence: 99%